The Implementation Of Authentic Assessment In Scoring Writing Task For The Student Of 8th Grade At SMP N 1 Surakarta - Kurniatun, Dewi; , Dra. Siti Zuhriah Ariatmi, M.Hum; , Drs. Djoko Srijono, M.Hum (2014)
This study aims at describing the ways is implemented in authentic assessment and techniques the teacher used to by score students' writing made by the students of SMP N 1 Surakarta. This research is descriptive qualitative research. The subject of the research is the student of SMP N 1 Surakarta at 8th C grade which consists of 26 students. The object of this research is authentic assessment is implementation for writing skill of the student of 8th grade at SMP N 1 Surakarta. The data are taken from student's worksheet book and teacher instruction. In this research the primary data are from the script of the writing task of the student and the second data are from analyzing document of the student writing task, and standard competence. The methods of collecting data in this research are observation, interview, and analyzing document. The research findings there are three kinds of the ways the teacher's assess of writing skill in authentic assessment through; classroom task, homework task, and written test by student worksheet and teacher instruction. The ways the teacher assesses of writing skill are by using aspects of authenticity. They are: classroom task and written test. For the first semester of 8th grade, the student learns simple short functional texts, such as: announcement and congratulating cards. Then, for long functional text the student learns are: descriptive text and recount text. To score the students writing tasks, a teacher should use rubric score. An ideal rubric score should cover the aspects, criteria, and the score.